The development of the Al-Qur'an and fardhu ain mastery model of the indigenous people in the state of Pahang Malaysia: the fuzzy delphi approach - Mustapha, Ramlan; Mokhtar, Nazatul Akmar; Ismail, Halim; Abdul Razak, Fahmi Zaidi; Abdul Rahman, Asmadi; Sh Othman, Sh Mohd Firdaus (Human Resource Management Academic Research Society (HRMARS), 2023)
This study aimed to get an agreement and expert views on the development Al-Quran and Fardhu Ain Mastery Model of the Orang Asli in the Pahang state region of Malaysia. This study employs the Fuzzy Delphi method using a 7 Likert scale to collect responses from 7 experts in various fields in Malaysia. A total of 21-item fuzzy questionnaire was given to experts for evaluation. Fuzzy Delphi Method was used for data analysis. Data were analyzed using triangular fuzzy numbering (triangular fuzzy number) and the position (ranking) of each variable is determined using the “defuzzification” process. The findings show that response and expert consensus on model elements are at a good level. The overall findings of the expert consensus agreement exceed 75%, the overall value of the threshold (d) < 0.2 and an α-cut exceeds 0.5. The priority factors were sorted by priority and were refined by adding and dropping items as recommended by experts.